The affinities of Proterochampsa barrioneuvoi Reig - Cruickshank, Arthur R I (Bernard Price Institute for Palaeontological Research, 1975)
Proterochampsa barrioneuvoi Reig is re-examined and is confirmed as a proterosuchian thecodont. None of the features previously thought to ally it to the Crocodilia are solely characteristic of that group. On the other hand it is not a phytosaur nor phytosaur ancestor, only showing one real trend towards these animals in the rearward migration of the internal and external nares. Proterochampsa and its relatives Chanaresuchus, Gualosuchus and Cerritosaurus are too late in time to be phytosaur ancestors. They are grouped together in the Proterochampsidae, a family within the Proterosuchia.
Keywords: archosauromorpha; crocodylomorpha; South Africa